Influence of weed management practices on growth and yield of aerobic rice (Oryza sativa L) - Ritesh Kumar Parihar; V.K.Srivastava; Alok Pandey; Vikram Kumar; Gaurendra Gupta (Annals of Agricultural Research, 2023)
A field experiment was conducted during Kharif 2014 at Agricultural Research Farm of Institute of Agricultural Sciences, BHU, Varanasi. The experiment consisted of eleven weed control treatments in randomized block design replicated thrice. Soil of the experimental field falls under sandy clay loam in texture and neutral in reaction with low in nitrogen and medium in available phosphorus and potassium. Results revealed that growth parameters viz., plant height (99.29 cm), number of tillers (500/m2 ), number of leaves (1500/m2 ), dry matter (165.37 g/meter row), yield attributes and grain yield (3.68 t/ha) were recorded highest with pre-emergence application of pendimethalin (30 EC) at 1.00 kg a.i./ha + bispyribac-Na (10% SC) at 35 g a.i./ha, which was at par with butachlor (50 EC) at 1.5 kg a.i./ha + bispyribac-Na (10% SC) at 35 g a.i./ha among chemical weed management practices while need based hand weeding recorded higher growth and yield characteristics among all the treatments.